Analysis of Validity and Practicality of Ethno-STEM Based Science E-Modules to Enhance Critical Thinking Skills and Independence of Students - Aditia, Kevin; Sarwanto, Sarwanto; Masykuri, Mohammad (Journal of Natural Science and Integration, 2024)
This study aims to assess the validity and practicality of the development of an ethno-STEM-based IPA (Natural Sciences) E-module in the theme of Jamu (traditional herbal drink) to train students’ critical thinking skills and independence. The research type is research and development (R&D) using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) instructional design. The research focuses on validity and practicality by using a questionnaire research instrument assessed by experts and practitioners with  Likert scale categories techniques. The data analysis results indicate that the e-module validity in the media aspect is 40.8, the material and learning aspects is 50.9, and the language aspect is 15. The validity is distributed within the very valid category. Additionally, the practicality of the e-module of a small group of students is 80 and teachers is 85.5 and it is distributed in the very practical category.  The operational practicality data suggest that student assessment is 76 or in the practical category and teacher is 82.5 or in the very practical category. The results of validity and practicality imply that the development of the ethno-STEM based science e-module in the theme of Jamu is valid and practical to be implemented to improve critical thinking skills in IPA learning.Keywords: critical thinking skills, e-module, independence, practicality, validity